Intersectionality theory and governmentality: bringing together what belongs together?. (1st December 2015) - ,
Abstract : The current care crisis and the increasing outsourcing of care work in the context of neoliberal reorganisation are major issues currently being addressed within feminist science. On the basis of these gendered characteristics of the new global division of labour, this theoretical article aims to bring two heavily discussed approaches in this field together: intersectional theory and the Foucauldian concept of governmentality. The article suggests that there are three different theoretical or methodological ways that these complex approaches might be combined. Discussing the mutual benefit, it then goes on to deal critically with the concept of intersectionality as a current dominant and widespread feminist theory, which tries to capture social complexity.